CHORISTOMAS AND TERATOMAS OF ORAL CAVITY - Baburathinam, Sona; Shyamsundar, Vidyrani; Babu.N, Aravindha; K, Masthan.K.M. (Journal of Biomedical and Pharmaceutical Research, 2019)
A cohesive tumor-like mass consisting of normal cells in an abnormal location constitutes a choristoma, while teratomas are considered as true neoplasms, consisting of tissues derived from all three germ layers. The occurrence of these lesions in the oral cavity is rare. They are considered in the differential diagnosis of reactive and benign lesions that commonly occur in the oral cavity. This article provides an overview of the various choristomas and teratomas that can occur in the oral cavity.